Enviro-toons : what do parents think about it? - Goh, Jeannette (2017)
In recent years there has been an increased societal focus on the detrimental effects that modernization has brought upon the environment, leading to more attention being put into solving these environmental issues. Studies that look into children being part of the solution have put out alarming results; their modernized childhoods have been increasingly alienated them from nature, an interaction that academics note to be key in helping children develop pro-environmental values. With children’s methods of learning growing increasingly dependent on media, it comes as no surprise that when academics needed to find out what children know about nature, they would turn to that outlet. Within children’s media, there has been an academic curiosity in the area of animated programming, called enviro-toons, shorthand for ‘environmental cartoons’. Because of its status as an animation, it has long been considered a lesser teaching tool in environmental education, especially when compared to more established teaching media like documentaries. There has been a recent academic research examining the content of these cartoons and acknowledging their potential to educate; yet there has been fewer studies done to see its impact on audiences in reality. This paper seeks understand enviro-toons within the context of Singapore, using the opinions of parents, to find out whether the use of these mediums could potentially impact their children. This focus on parents is not only due to their ability to govern their young children’s accessibility to these enviro-toons, but also because of their understanding of their children’s current media habits which allowed them to discuss about possible further ways in which their children can learn from this medium. Consequently, understanding the opinions of parents can give an insight into the implementation of enviro-toons within a child’s environmental education. Using a phenomenological framework to examine the face-to-face interviews with 10 parents, this paper found that parents were cautiously optimistic about the medium, where they all saw its potential to teach but saw the need for sources outside this media to ensure that the environmental message is received by their children. Parents saw enviro-toons as capable of educating through their humorous and simplified storylines that keep children in their seats, not only giving children a motive to view the medium and its message in its entirety, but also acts as an example of the issue that is being discussed. On the other hand, parents also pointed out a lack of understanding of the importance of the environmental themes by their children, where parents recommended the need for the repetition of the medium, choosing those with issues that are relevant to their child’s life, that will help their children overcome this hurdle. Parents also stressed the importance of the use of the enviro-toon within a greater network of environmental educators outside the home, like the school and the government, that will help drive the environmental message home.